Modeling-aided coupling of catalysts, conditions, membranes, and reactors for efficient hydrogen production from ammonia. Issue 5 (17th February 2023) - Realpe, Natalia; Kulkarni, Shekhar R.; Cerrillo, Jose L.; Morlanés, Natalia; Lezcano, Gontzal; Katikaneni, Sai P.; Paglieri, Stephen N.; Rakib, Mohammad; Solami, Bandar; Gascon, Jorge; Castaño, Pedro
Abstract : Our agnostic model led us to identify optimized combinations of catalyst–conditions–membrane–reactor for maximum hydrogen production from ammonia decomposition. Abstract : The production of high-purity, pressurized hydrogen from ammonia decomposition in a membrane catalytic reactor is a feasible technology. However, because of the multiple coupled parameters involved in the design of this technology, there are extensive opportunities for its intensification. We investigated the coupling between the type of catalyst, process conditions, type of membrane, and reactor operation (isothermal and non-isothermal) in the catalytic decomposition of ammonia. First, we developed an agnostic dimensionless model and calculated the kinetic parameters for a set of lab-made Ru- and Co-based catalysts and the permeation parameters of a Pd–Au membrane. The non-isothermal model for the Pd–Au membrane reactor was validated with the experiments using Co-based catalysts. Finally, we analyzed the coupling conditions based on the model predictions, results obtained in the literature and our experimental results, including several case studies. The thorough analysis led us to identify optimized combinations of catalyst–conditions–membrane–reactor that yield similar or improved results compared to the ones of Ru-based catalyst in a non-membrane reactor. Our results indicate that optimizing a single factor, such as the catalyst, may not lead to the desired outcome and a more holistic approach is necessary to produce pressurized and pure hydrogen efficiently.